Purpurin binding interacts with LHPP protein that inhibits PI3K/AKT phosphorylation and induces apoptosis in colon cancer cells HCT‐116. Issue 3 (28th December 2020) - Li, Zhiwen; Zhou, Xu; Zhu, Huaqiang; Song, Xie; Gao, Hengjun; Niu, Zheyu; Lu, Jun
Abstract: Colorectal cancer (CRC) is the leading type of diagnosed cancer; globally, it resides in the fourth‐leading origin of cancer‐interrelated mortality in the globe. The treatment strategies were chemotherapy and potent radiotherapy. Although chemotherapy treatment can eliminate tumor cells, it remains with unnecessary toxic effects in cancer patients. Therefore, the identification of natural‐based compounds, which have selectively inhibiting target proteins with limited toxicity that can facilitate the therapeutic approaches against CRC. In this existing approach, which highlights the binding efficacy of our anthraquinone compound, purpurin against phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) protein restrains the CRC cell growth by inhibiting phosphatidylinositol‐3‐kinase/protein kinase B (PI3K/AKT), cell proliferation, and inducing apoptosis signaling. Primarily, purpurin (36 μM) exposed to HCT‐116 cells and incubated for 24 and 48 h could induce reactive oxygen species production, subsequently alter mitochondrion membrane, and increase the apoptotic cells in HCT‐116. LHPP, a kind of histidine phosphatase protein, has been considered as a tumor suppressor in numerous carcinomas. However, purpurin‐mediated LHPP proteins and its associated molecular events in CRC remain unclear. In our docking studies revealed that purpurin has been strongly interacts with LHPP via hydrophobic and hydrophilic binding interaction. Western blot results confirmed that purpurin enhances the expression of LHPP protein, thereby inhibits the expression of phosphorylated‐PI3K/AKT, EGFR, cyclin‐D1, PCNA in HCT‐116 cells. Moreover, purpurin induces messenger RNA expression of apoptotic genes (Bax, CASP‐9, and CASP‐3) in HCT‐116 cells. Thus, we conclude that purpurin could be a natural and useful compound, which inhibits the growth of CRC cells through the activation of LHPP proteins.